Muscle activation levels in the lower leg during weight-bearing functional tasks on unstable surfaces in patients with percutaneous Achilles tendon repair. - Tan, Firat; Guney-Deniz, Hande; Doral, Mahmut Nedim (Physiotherapy Theory & Practice, 2025)
Background: Achilles tendon rupture (ATR) is a common injury that affects functional capacity and neuromuscular control of the lower limb. While exercise interventions after ATR are frequently prescribed, there is limited evidence regarding muscle activation demands during weight-bearing tasks on different balance surfaces in long-term post-operative individuals. Objective: To compare lower leg muscle activation levels and co-contraction patterns during functional tasks performed on various balance platforms in individuals with a history of percutaneous ATR. Methods: Nineteen recreationally active males (mean age 40.6 ± 7.2 years) who underwent unilateral percutaneous ATR approximately 5.0 ± 4.8 years prior to testing were recruited. Surface electromyography (%MVIC) was recorded from the peroneus longus (PL), tibialis anterior (TA), medial and lateral gastrocnemius (GM, GL), and soleus (SL) during Single-Leg Stance (SLS), single-leg squat (SLSQ), and forward lunge (FL) performed on flat ground, wobble board, stability trainer, and BOSU®. TA:GM and TA:SL co-contraction ratios were calculated. All subjects performed the functional tasks barefoot. Results: The BOSU surface elicited the highest %MVIC in all muscles, particularly during SLS (e.g. PL: 44.8 ± 15.5; GM: 36.6 ± 12.7). FL and SLSQ on flat ground induced lower gastrocnemius activation. Co-contraction ratios were significantly higher in SLSQ and FL compared to SLS (p <.001), indicating more balanced dorsiflexor – plantarflexor engagement during dynamic tasks. Conclusion: Muscle activation and co-contraction patterns vary by functional task type and surface. These findings may assist physiotherapists in prescribing functional progression exercises based on neuromuscular demand profiles after ATR.